Implementación de un sistema de costos por procesos en la heladería artesanal de la hostería “Imperio Real”, ubicada en el cantón Salcedo provincia de Cotopaxi. - Aimacaña Casnanzuela, Maura Janeth (2019)
The problem faced by artisanal microenterprises currently is the empirical management of accounting information, generating ignorance of the elements involved in the process to obtain the real cost and the profit margin of the finished products. For this reason, this integrative project aims to implement process cost system in the “Real Ice Cream” artisanal ice cream parlor, belonging to the “Imperio Real” Inn, located in the Salcedo City, Cotopaxi Province. For which it was necessary to place a quantitative research approach, bibliographic type in the first part and then in the field allowing to obtain primary information, directly from the owner and personnel in charge of manufacturing the product, using the deductive method the cost system was designed by processes though the identification of the cost elements involved in each phase of the production of artisanal ice cream, suppoted by techniques such as the observation verifying each product process and the interview the was applied to the owner of the “Imperio Real” Inn, allowing the collection of data the development of the project. The results obtained through the application of the Process Cost System, it was possible to determine the real value of each phase, the unit cost of production and the profit margin of the finished product. A warning system was also carried out in the inventory that allows determining the existing raw material in the warehouse, where the color cell is activated, verifying that the materials do not decrease according to the minimum required for the manufacture of the product, helping to eliminate wasted time in the acquisition of inputs for the production of artisanal ice cream, in addition the system was socialized in the excel program to the owner for its efficient use.